Durability of pervious concrete using crushed seashells. (15th March 2017) - Nguyen, Dang Hanh; Boutouil, Mohamed; Sebaibi, Nassim; Baraud, Fabienne; Leleyter, Lydia
Highlights: The crushed seashells can be used as a replacement in the pervious concrete composition, for low-volume roads. The freeze/thaw performance of shells concretes is considerably more weakly than the control pervious concrete. The blended of silty clay sand as clogging agent causes a significant decrease in permeability of pervious concrete, especially for shells concretes. The chemical characteristics of crushed shells have an influence remarkable on the freeze thaw durability of pervious concrete. Abstract: Pervious concrete is one of the most important emerging technologies for sustainable facilities and infrastructure. Significant research and development have been carried on pervious concrete; however, the durability of the pervious concrete remains a challenge. In this study, the durability of pervious concrete, with or without the crushed seashells, are studied by: freeze-thaw resistance test with and without deicing salt, clogging test and leaching test. The shell pervious concrete was created by replacing 60% mass of the natural aggregates in control pervious concrete by crushed seashells. The freeze-thaw resistance of the shell pervious concrete is lower than the control pervious concrete and it was not proportional with the mechanical strength. In addition, a blended material with silty clay and sand as a clogging agent causes a significant decrease on the drainage capacity of pervious concrete. However, the pervious concretes remains permeably even after the clogging (k > 0.5 mm.s −1 ). Furthermore, the leaching of pervious concretes occurs quickly after contacting with demineralized water. This experiment showed also that some chemical characteristic (chloride ion and organic matter content) of crushed shells could have more influence on the durability than the physical and mechanical properties of pervious concrete. As a final, this article shows an acceptable durability of pervious concrete with and without crushed shells for the application of low traffic load.